The Effectiveness of the Elderly Integrated Healthcare Center Program to Improve Elderly Health: Efektifitas Program Posyandu Lansia Guna Meningkatkan Kesehatan Lansia - Prisca, Olivia Ingkan; Agustina, Isna Fitria (Universitas Muhammadiyah Sidoarjo, 2024)
The study